Production and quality of pineapple juice with mint powder by foam-mat drying - Gonzaga, Bruna Beatriz Nascimento; Coelho, Bruno Emanuel Souza; de Sousa, Karla dos Santos Melo; Araújo, Samuel Gonçalves de; Duarte, Valéria Medrado; da Silva, Laurenielle Ferreira Moraes (Comunicata Scientiae, 2021)
The objective of this work was to produce pineapple juice with powdered mint, using the foam layer drying process, and to evaluate the quality of the final product. For the formation of the foam, 2% (w/w) of Super Liga Neutra and Emustab were added to the pineapple and mint juice and subjected to agitation in a domestic mixer for 15 minutes; then, it was spread on trays forming a thin layer of 1.0 cm thick whose drying conditions were 60, 70 and 80 ºC. With the experimental data of the drying kinetics of pineapple and mint juice, drying curves were drawn whose models adjusted to the data were: Exponential of two terms, Henderson & Pabis and Page. The final product was evaluated for pH parameters, titratable acidity, water content, total solids, soluble solids, ascorbic acid, solubility, and color (L *, a * and b *). The Page model was the one that best fit the experimental data on the drying of pineapple juice with mint, at all temperatures, as it has a higher coefficient of determination (R²), indicating that this model satisfactorily represents the drying phenomenon of pineapple with mint. It was evidenced that, the increase of the drying temperature, resulted in the reduction of acidity and water content, and at the same time an increase in the content of soluble solids. And, the samples dehydrated at a temperature of 70 ºC showed greater stability in the ascorbic acid content, and less darkening.